Adjuvant Hormonal Therapy in Postmenopausal Women with Breast Cancer: Physician’s Choices - Asim Jamal Shaikh; Shiyam Kumar; Sajjad Raza; Maria Mehboob; Osama Ishtiaq (International Journal of Breast Cancer)
The choice of adjuvant hormonal therapy in postmenopausal women with hormone receptor positive breast cancer has remained a matter of controversy and debate. The variety of agents is available, with each claiming to be superior. This clinical survey was undertaken to get an impression of the physician’s first choice of therapy in an attempt to find out what questions still need to be answered in the making of “standard of care.” A web-based clinical survey was sent to the cancer physicians around the world, and 182 physicians responded to the survey. Most were medical oncologists in a tertiary care hospital. 36.3% preferred Anastrozole, 35.2% Tamoxifen, and 22.2% Letrozole as their first choice. Data support (67.8%) and safety concerns (30%) were given as the main reasons for the choice, 63.7% switched their therapy, and 24% had to switch because of side effects. 73.6% used 5 years of adjuvant hormonal therapy, 6.6% for 7 years, and 4.4% for 10 years. 61.5% follow their patients 3 times monthly, and 73.2% used laboratory and radiological assessment at each followup. Conclusion. Physicians show disagreement over the choice and duration of hormonal therapy in this patient population. Clinical trials leading to firm recommendations to set standards from which patients benefit the most are needed.